2018
DOI: 10.1186/s12888-018-1935-0
|View full text |Cite
|
Sign up to set email alerts
|

Persistent catatonia following epileptic seizures: a case report and systematic literature search

Abstract: BackgroundCatatonia is frequently associated with mood and psychotic disorders as well as with general medical conditions, especially with seizures. In the case of the latter, catatonia mostly resolves when the seizures respond to the anticonvulsive treatment. We report, to our knowledge, the first case of a patient without affective or psychotic disorder, who developed catatonia in the postictum and whose catatonia did not resolve with anticonvulsive treatment, but did so with lorazepam.Case presentationWe de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
1
0
5
Order By: Relevance
“…In some reports of concurrent catatonia and seizures, catatonia was considered as a seizure semiology itself (ictal catatonia), 47 - 50 but in other reports, catatonia and seizures were viewed as distinct phenomena. 51 - 56 Our patient was clearly predisposed to recurrent catatonia on account of schizoaffective disorder. A positive history of head injury also suggested that he was developing a predisposition for seizures (epilepsy).…”
Section: Discussionmentioning
confidence: 75%
“…In some reports of concurrent catatonia and seizures, catatonia was considered as a seizure semiology itself (ictal catatonia), 47 - 50 but in other reports, catatonia and seizures were viewed as distinct phenomena. 51 - 56 Our patient was clearly predisposed to recurrent catatonia on account of schizoaffective disorder. A positive history of head injury also suggested that he was developing a predisposition for seizures (epilepsy).…”
Section: Discussionmentioning
confidence: 75%
“…Kahlbaum descreveram pela primeira vez a catatonia como um conjunto de sintomas psicomotores em sua publicação intitulada "Die Katatonie oder das Spannungsirresein". Nessa obra, a principal característica atribuída à catatonia foi um estado de extrema tensão (VERBRAEKEN;LUYKX, 2018).…”
Section: Resultsunclassified
“…Por fim, o quarto tipo é a catatonia periódica, caracterizada pelo retorno cíclico dos sintomas de catatonia. Esses episódios duram em média de quatro a dez dias e podem recorrer semanas ou anos depois (VERBRAEKEN;LUYKX, 2018).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Két páciensnek dystoniás, egynek komplex parciális rohama, egynek pedig absence status epilepticusa volt. Egy esetleírásban epilepsziás rohamot követően kialakult, perzisztáló cataton állapotról számoltak be, amely antiepileptikumra nem, csak lorazepámra reagált [17].…”
Section: Epilepsziaunclassified